Australian children's independent mobility levels: secondary analyses of cross-sectional data between 1991 and 2012 - Schoeppe, S.; Tranter, P.; Duncan, M.; Curtis, Carey; Carver, A.; Malone, K. (Routledge, 2016)
This study investigated changes in Australian children's independent mobility levels between1991 and 2012. Data from five cross-sectional studies conducted in 1991, 1993, 2010, 2011 and 2012 were analysed. Parent and child surveys were used to assess parental licences for independent mobility and actual independent mobility behaviour in children aged 8–13 years. Findings show declines in the proportion of young children (=10 years of age) being allowed to travel home from school alone (1991: 68%, 1993: 50%, 2010: 43%, 2011: 45%, 2012: 31%) and travel on buses alone (1991: 31%, 1993: 15%, 2010: 8%, 2011: 6%, 2012: 9%). Furthermore, the proportion of children travelling independently to school decreased (1991: 61%, 1993: 42%, 2010: 31%, 2011: 32%, 2012: 32%). Significantly fewer girls than boys travelled independently to school at each time point (p?=?.001). Overall, the findings suggest that Australian children's independent mobility levels declined between 1991 and 2012.